2014
DOI: 10.1002/chem.201403267
|View full text |Cite
|
Sign up to set email alerts
|

Super Sensitization: Grand Charge (Hole/Electron) Separation in ATC Dye Sensitized CdSe, CdSe/ZnS Type‐I, and CdSe/CdTe Type‐II Core–Shell Quantum Dots

Abstract: Ultrafast charge-transfer dynamics has been demonstrated in CdSe quantum dots (QD), CdSe/ZnS type-I core-shell, and CdSe/CdTe type-II core-shell nanocrystals after sensitizing the QD materials by aurin tricarboxylic acid (ATC), in which CdSe QD and ATC form a charge-transfer complex. Energy level diagrams suggest that the conduction and valence band of CdSe lies below the LUMO and the HOMO level of ATC, respectively, thus signifying that the photoexcited hole in CdSe can be transferred to ATC and that photoexc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 46 publications
1
51
0
Order By: Relevance
“…In our previous investigation, we have demonstrated ultrafast interfacial electron‐transfer dynamics with a series of TPM dyes with different molecular structures and coupling . We have also reported CT dynamics with TPM‐dye‐sensitized CdSe and CdS QDs and found that a TPM‐dye–QD composite can act as a super‐sensitizer in a QD solar cell …”
Section: Introductionmentioning
confidence: 92%
“…In our previous investigation, we have demonstrated ultrafast interfacial electron‐transfer dynamics with a series of TPM dyes with different molecular structures and coupling . We have also reported CT dynamics with TPM‐dye‐sensitized CdSe and CdS QDs and found that a TPM‐dye–QD composite can act as a super‐sensitizer in a QD solar cell …”
Section: Introductionmentioning
confidence: 92%
“…In addition to that lower QD loading on TiO 2 surface (as compared to dye loading in DSSC) resulting direct electron transfer from TiO 2 film to the oxidized redox couple in photo anode. However exciton dissociation through hole transfer is not widely reported in literature except few recent reports by us [26][27][28][29] and Kamat & co-workers 30 . Electron injection is much faster as compared to hole transfer, so for efficient devices hole has to extracted from QD surface as fast as possible 20 .…”
Section: Introductionmentioning
confidence: 96%
“…Also, in the case of CdSe/CdTet ype II coreshell particles, emission quenching takes place in the presence of 4NP (electron quencher), in which electrons are supposed to localize in the CdSe core (Figure 4f and f'). In our earlier investigation, we have observed that both electron and hole transfer processes from photoexcited QDs to the molecular adsorbatesc an take place on an ultrafast timescale, [24,44,45] which cannot be accounted for by time-resolved emissionq uenching studies. The emission spectrum of the CdSe/ CdTet ype II core-shell particles is broader,r elative to that of CdSe/CdSq uasi-type II core-shell particles, which showse mission maximaa tl = 575 nm with as houlder at l = 555 nm.…”
Section: Scheme2a)mentioning
confidence: 96%
“…[44] It shouldb en oted that, althoughe lectrons are delocalized throughout the CBs of both CdSe and CdS in the NC, electron wavefunction overlap between CdSe and 4-NP will be much higher than that of CdSe/CdS and 4-NP composite. B) Schematic illustration of cascading hole transfer from the CdTeshell to 4MP and also cascading from the CdSe core to the CdTes hell and finally to 4MP,and electron transfer from the CdTes hell to 4NP and also leaking from the CdSe core through the CdTes hell to 4NP.…”
Section: Scheme2a)mentioning
confidence: 99%
See 1 more Smart Citation